ROYAL MAUSOLEUM AS HERITAGE TOURISM IN VIRTUAL REALITY USING GEOSPATIAL INFORMATION SYSTEMS (GIS) OF PERAK TENGAH DISTRICT - Omar, Fatin Nabilah; Abdul Rahman, Norainah; Abdullah, Kamariah (Jurnal ’Ulwan, 2023)
Perak Tengah District has the potential to benefit from heritage tourism. The main problem there is no tourism database for the royal mausoleums in Perak Tengah District for heritage tourism. The aim of develop tourism trails of royal mausoleums in Perak Tengah presented in the Virtual Reality (VR) using Geospatial Information Systems (GIS) with three objectives which are (i) to identify tourism trails of Royal Mausoleums in Perak Tengah district, (ii) to evaluates the adequacy of support facilities and conditions of heritage tourism and (iii) to recommend VR using GIS as new contemporary forms of technology. The study begins by identifying secondary data determining the description and history of royal mausoleums in Perak Tengah. Observation survey will be used in this study as qualitative research, which to identify mausoleums in the Perak Tengah District and the evaluations the adequacy of support facilities and infrastructures. A software QGIS are used to locate and mapping the distribution of mausoleums in Perak Tengah District. According to the findings, 16 mausoleums and 1 museum of Kompleks Sejarah Pasir Salak have been located within the study area. By using coordinates made up of graphic data, the results of the identification of the distribution of tourism products are projected on a map and Google Earth. In the findings, 16 mausoleums adequate with support facilities and infrastructure especially road access, signages and wayfinding. The further studies should consider and investigation of components a VR and GIS that would help local authorities or stakeholders take advantage of this technology for promotion tools.